1973
DOI: 10.1021/jo00948a023
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of aromatic thiol esters

Abstract: The photolysis of a variety of aromatic thiol esters was investigated in cyclohexane using a 254-nm light source.The photochemical reaction proceeds initially by cleavage of the S-acyl bond, giving rise to the corresponding aromatic thiyl radical and an acyl radical which sometimes decarbonylates. The resulting radicals recombine to give disulfides, sulfides, and hydrocarbons. Acyl radicals which are less prone to decarbonylation abstract hydrogen to form aldehydes. No photo-Fries rearrangement and a minor amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

1974
1974
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 3 publications
0
21
0
1
Order By: Relevance
“…Following preliminary reports on the successful photochemical and thermal homolytic cleavage of the acyl-SPh bond in S-phenyl thiobenzoate, [120][121][122] Penn and Liu introduced the S-(2-naphthyl) thioesters as convenient photochemical sources of acyl radicals. 123 White light photolysis of these readily prepared substances, in the presence of cyclohexa-1,4-diene as a hydrogen donor, resulted in excellent yields of the corresponding aldehydes for a range of aromatic, primary, secondary, and tertiary acid derivatives (Scheme 13).…”
Section: Acyl Radicals From Thioesters and Related Species (Rco−sr′)mentioning
confidence: 99%
“…Following preliminary reports on the successful photochemical and thermal homolytic cleavage of the acyl-SPh bond in S-phenyl thiobenzoate, [120][121][122] Penn and Liu introduced the S-(2-naphthyl) thioesters as convenient photochemical sources of acyl radicals. 123 White light photolysis of these readily prepared substances, in the presence of cyclohexa-1,4-diene as a hydrogen donor, resulted in excellent yields of the corresponding aldehydes for a range of aromatic, primary, secondary, and tertiary acid derivatives (Scheme 13).…”
Section: Acyl Radicals From Thioesters and Related Species (Rco−sr′)mentioning
confidence: 99%
“…Furthermore, aphotocatalyst solely servinga sH AT withoutp hotoredox or energy-transfer capacityi sc riticalb ecause they can activate thioesters to produce acyl radicals. [16] Studies have shown that bond dissociation enthalpy (BDE) considerations are less important than CÀHb ond polarity in HAT. [14] Benzophenones and quinonesh ave been used for HAT.…”
mentioning
confidence: 99%
“…In our continuing effort on developing organocatalytic processes, we pursued to explore organic dyes as promoters. [16] We therefore conceived that direct hydrogen abstraction of highlyp olarized CÀHb ond of aldehyde by using this class of activators with weak visible light might be possible. [15] Nonetheless, they mediated HATg enerally carried out under UV light.…”
mentioning
confidence: 99%
“…The photo-Fries reaction is fairly general for aromatic systems and usually leads to compounds derived from rearrangement of the initially formed biradicals to ortho and para products in a solvent cage. [7] The photo-Fries rearrangement is rather common with esters and amides and, as far as sulfur compounds are concerned, it has been observed with thiol esters [8] and sulfenanilides. [9] On the other hand, examples concerning aromatic disulfides are very rare; [10] it is also extremely unusual to encounter rearrangements exclusively affording ortho products.…”
Section: Resultsmentioning
confidence: 99%